Pengaruh Fashion Involvement dan Shopping Lifestyle Terhadap Impulse Buying Produk Fashion Shopee ( studi kasus Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Malang Anggalatan 2016-2028 - Wulan Alimudin; N. Rachma (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACKThis study examines and analyzes the effect of fashion involvement and lifestyle shopping partially or simultaneously. The purpose of this study was to determine the effect of Fashion Involvement on impulse buying, the influence of shopping lifestyle on impulse buying and the effect of fashion involvement and Shopping Lifestyle on Impulse Buying of fashion shopee products, a case study of students from the Faculty of Teacher Training and Education at Malang Islamic University. The sampling technique used in this study was convenience sampling with the criteria of students aged 19 to 24 years old and making unplanned purchases on shopee fashion products. with the number of respondents set was 60 people. The data analysis method used is multiple linear regression analysis. Based on the research results, partial fashion involvement has a significant effect on impulse buying, and the shopping lifestyle variable has a significant effect on impulse buying. From the simultaneous test results, the variables fashion involvement and shopping lifestyle have a significant effect on impulse buying..Keywords : Fashion Involvement, Shopping Lifestyle, Impulse Buying.